2019
DOI: 10.4103/sjg.sjg_566_18
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive coping, low self-efficacy and disease activity are associated with poorer patient-reported outcomes in inflammatory bowel disease

Abstract: Background/Aims: Patient-reported outcomes (PRO) are key aspects in the management of inflammatory bowel disease (IBD). This study aims to evaluate factors associated with adverse PRO, including modifiable social constructs of maladaptive coping and self-efficacy as well as physician–patient concordance on PRO. Patients and Methods: This cross-sectional study was performed in patients with Crohn's disease (CD) or ulcerative colitis (UC) from September 2015 to March 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[ 1 ] TNFi are generally well tolerated and result in a significant improvement of patients' reported outcomes. [ 2 ] However, a wide range of adverse events have been reported in the literature including hematological, neoplastic, neurological and infectious complications. [ 3 ] One of the most commonly reported side effects are infectious events.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] TNFi are generally well tolerated and result in a significant improvement of patients' reported outcomes. [ 2 ] However, a wide range of adverse events have been reported in the literature including hematological, neoplastic, neurological and infectious complications. [ 3 ] One of the most commonly reported side effects are infectious events.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examine the relationship between health-related quality of life (HRQoL) and coping strategies, demonstrating a statistically significant correlation between the two variables [ 11 , 12 , 13 , 14 , 15 , 17 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 30 , 32 , 36 , 37 , 38 , 40 , 41 , 42 , 44 , 45 , 48 , 49 , 55 , 56 , 58 , 61 , 62 , 66 ]. Specifically, maladaptive coping strategies, such as acceptance–resignation, negative religious coping, catastrophizing, passive coping, low acceptance, perceived control, decreased cognitive flexibility, and emotion-focused coping, were all associated with lower HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…Chao et al found that both disease activity and maladaptive coping negatively affected HRQoL [ 13 ]. Patients with higher self-efficacy were more likely to report the use of adaptive coping strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation